PENGEMBANGAN PANGAN FUNGSIONAL BUBUR INSTAN RENDAH INDEKS GLIKEMIK BERBASIS PANGAN LOKAL - Mado, Juenita Elfunam; Rawung, Dekie; Taroreh, Mercy (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2020)
AbstractThe purpose of this study was to analyze the nutritional content and glycemic index value of local food-based instant porridge products. The research method used was experimental research with the determination of the glycemic index using a one-shot case study design on a sample of white rats (Rattus novergicus). The results obtained in this study are the glycemic index value of instant porridge which is included in the low GI category, namely goroho plantain 31,88, baruk sago 39,43, and "mulubebe" plantain instant porridge 43,35. Meanwhile, instant porridge that has medium GI is mocaf 59,34. The results of the calculation of the glycemic load of instant porridge which has a low glycemic load are goroho plantain 8.17, while those which have a moderate glycemic load are "mulubebe" plantain 11.88, baruk sago 12.02 and mocaf 17.16 . So that the use of carbohydrate sources from different local foods, namely goroho plantain flour, â€œmulubebeâ€ plantain flour, baruk sago flour, mocaf flour in instant porridge affects the glycemic index value of instant porridge.Â Keywords: Instand porridge, glycemic index, plantain, mocaf, sago.